PENGEMBANGAN MEDIA BOOKLET PADA MATERI PERUBAHAN CUACA BERBASIS AUGMENTED REALITY MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS III SEKOLAH DASAR - Iswan, Muhammad; Alfi, Cindya; Fatih, Mohamad (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
Integrated thematic learning is learning that is packaged in themes based on the integrated learning content. The aim of this research is to develop Augmented Reality-based Booklet media in order to further improve critical thinking skills of class III elementary school students. This research applied the research and development (R&D) method with ADDIE model which consists of 5 steps, namely analysis, design, development, implementation and evaluation. The instruments in this research are observation, interviews, tests and questionnaires. The data analysis technique used is quantitative descriptive analysis technique. The research results of this study can be seen from the average results of media experts for Augmented Reality-based Booklet media getting 4.95 which is stated "very feasible", the assessment of material experts getting 4.46 which is stated as "very feasible", and the assessment of language experts getting 4.4 which is stated "very decent". Based on the effectiveness of the media, teachers' responses received an average of 4.8 which was stated "very effective" while the pre-test and post-test results of class 3 students using the N-Gain test received an average of 0.87 in the "high" category. Based on the results of this research, it can be concluded that research and development of augmented reality-based booklet media can improve the critical thinking skills of third grade elementary school students.